Shear behavior of autoclaved aerated concrete confined masonry walls with different scales - Varela-Rivera, Jorge; Cancep-Rodriguez, Juan; Fernandez-Baqueiro, Luis; Moreno Herrera, Joel Alberto (Revista ALCONPAT, 2024)
An experimental study on the shear behavior of autoclaved aerated concrete (AAC) confined masonry walls is presented. A total of five reduced-scale walls were tested in the laboratory under reverse lateral loads. Variables studied were the geometric scaling factor and the aspect ratio of walls. Scales considered were 1:2 and 1:3. Based on the behavior of the reduced- and corresponding full-scale walls experimental scaling factors were determined. Existing geometric scaling factors were compared with corresponding experimental scaling factors. It was concluded that geometric scaling factors can be used to predict the shear strength and maximum shear strength of walls with scales of 1:2 and 1:3. Geometric scaling factors can only be used to predict stiffness and drift ratios associated with the maximum shear strength of walls.